HLA and age of onset in myasthenia gravis - Santos, Ernestina (2018)
The aetiology of MG is unknown, but both genetic and environmental factors are important. Over the years association of MG with Human Leucocyte Antigens (HLA) has been described in different populations. We investigated a possible association between HLA-DRB1 alleles and age of onset in MG. One hundred and fourteen MG patients (82 females) and 282 control individuals (CP) were studied. Patients were classified according to the age of onset (early-onset <50, n = 74 and late-onset ≥ 50, n = 20). Patients with thymoma (n = 20) were analyzed separately. HLA-DRB1 and HLA-B*08 genotyping was performed using PCR-SSP methodology. HLA-DRB1*03 allele was overrepresented in the global MG. When the early-onset subgroup was considered, this association became even stronger. Regarding the late-onset subgroup, the frequency of HLA-DRB1*01 allele was higher than in the CP. For the thymoma subgroup, the HLA-DRB1*10 allele frequency was significantly higher when compared to the CP. These results have shown a strong association of HLA-DRB1*03 with MG, especially for EOMG also in our population. HLA-DRB1*01 was associated to LOMG suggesting that is a susceptibility factor for this subgroup of the disease. This study confirms a different genetic background of MG subgroups regarding age of onset.